On Optimal Frequencies for Reconstruction of a One-Dimensional Profile of Gradient Layer’s Refractive Index - Dmitrii Tumakov (International Journal of Optics)
The problem of reconstruction of a one-dimensional profile of gradient layer’s refractive index is investigated. An algorithm for choosing a right frequency, at which a scattered field is measured, is proposed. It is concluded that at the correct choice of frequency one measurement must be sufficient. Moreover, in this case, regularization parameters of the residual functional are chosen as zero. It is shown that in case of measurements being carried out with errors, residual terms must be added to the functional.